2016
DOI: 10.1007/s00127-016-1299-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychological factors on recovery from injury: a multicentre cohort study

Abstract: PurposeUnintentional injuries have a significant long-term health impact in working age adults. Depression, anxiety and post-traumatic stress disorder are common post-injury, but their impact on self-reported recovery has not been investigated in general injury populations. This study investigated the role of psychological predictors 1 month post-injury in subsequent self-reported recovery from injury in working-aged adults.MethodsA multicentre cohort study was conducted of 668 unintentionally injured adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 46 publications
(59 reference statements)
5
43
0
Order By: Relevance
“…patients better manage these conditions as well as timely referral to appropriate services as necessary. 23,24 In our cohort, higher OMPSQ scores at baseline was an independent predictor of higher pain ratings during the 12 month follow-up. This is plausible as the OMPSQ has been promoted as a tool to screen for psychosocial risk factors associated with delayed recovery; and a recent systematic review 18,27 showed that the OMPSQ has reasonable or moderate predictive ability in identifying persons at risk of developing chronic pain.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
See 1 more Smart Citation
“…patients better manage these conditions as well as timely referral to appropriate services as necessary. 23,24 In our cohort, higher OMPSQ scores at baseline was an independent predictor of higher pain ratings during the 12 month follow-up. This is plausible as the OMPSQ has been promoted as a tool to screen for psychosocial risk factors associated with delayed recovery; and a recent systematic review 18,27 showed that the OMPSQ has reasonable or moderate predictive ability in identifying persons at risk of developing chronic pain.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…36 It is important to note, however, that healthcare professionals routinely treating people with mild/ moderate injuries are not mental health experts. 24 Hence, one judicious clinical implication of this study would be that non-mental health professionals be trained to identify patients at risk of poor recovery using brief self-report measures of psychological health and pain, so as to help…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Patients report anxiety, sadness and discouragement, even depression. This shows that emotional distress is caused by the ICU, which instigates and strengthens feelings of negativity [17][18]7]. When these feeling are associated with the presence of wounds, major effects on the customer coping ability are seen, once weakened by the peculiarities of this sector.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to anxiety related to the treatment and delay in the evolution of wound healing. This can lead to depression because the damage is not only physical, but a stigma resonates in interpersonal and family relationships [5,[6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Workers who have experienced a physical workplace injury are at high risk of developing secondary mental health conditions: recent data suggest that up to half develop depressive symptoms within a year of injury 1 2. Secondary mental health problems negatively impact long-term recovery and return to work (RTW) 3 4. Therefore, there is a strong need for consistent and effective mental health screening, referral and treatment among those experiencing occupational injuries, yet it is not clear whether this need is being met.…”
Section: Introductionmentioning
confidence: 99%